The Discourse of Digital Inclusion of Women in Rwanda’s Media - Jjuuko, Margaret; Njuguna, Joseph (Amsterdam University Press., 2019)
Rwanda has positioned ICTs towards its vision for an all-inclusive society. These tools are critical for empowering women and the youth, the envis-aged key participants in the knowledge society. While Rwanda’s news media is replete with stories on the potential transformational effects of ICTs on women, how they represent the discourse on women’s digital inclusion in the Rwandan context has not been explored. Departing from the philosophy that news media routinely af f irm the reinforcing dominant public norms and values, this chapter explores how two Rwandan dailies represent the digital inclusion by examining the themes and news sources in ICT stories on women. Findings reveal that the media depict Rwandan women’s digital inclusion as attainable through capacity building, literacy, participation, speed in embracing ICTs, and mindset change.
Keywords: Women; Digital inclusion; Digital divide; The New Times